Study On Mechanical, Biodegradability And Compostability Of Agriculture Waste Loaded Biodegradable Polymer - Tan, Boey Wei (Universiti Sains Malaysia, 2022)
Biodegradable polymer is the best solution to reduce white pollution issues. Poly(butylene adipate-co-terephthalate) (PBAT) exhibit good biodegradability and mechanical properties, but its high cost limits its wide applications. The incorporation of natural fillers into PBAT can significantly lower the cost, but the mechanical properties of the obtained PBAT/filler composites are dramatically reduced. Herein, the mechanical properties of compatibilized PBAT composites with using modified starch (MS), alkaline treated rice husk (ATRH) and hybrid filler; MS and ATRH by simple melt-blending method was investigated. Besides, various characterization techniques including FTIR, SEM, DSC, water absorption, water contact angle, tensile testing and oxygen transmission rate test will be performed on the composite. Then, the biodegradability will be evaluated by measuring weight lost during soil burial test. The composability of the PBAT composite will be carried on measuring the height of onions seeds and seed germination rate in the pot for the duration of 25 days. In this research, the results showed that the mechanical properties of PBAT/modified starch received remarkable mechanical properties (TS:8.027MPa; YM:67.938MPa; EAB: 202.585%) followed by hybrid filler loading (60PBAT/30MTS/30S/10ATRH) with (TS:7.384MPa; YM:83.211MPa; EAB: 28.59%) and finally the PBAT/alkaline treated rice husk with (TS:9.975MPa; YM:179.693MPa; EAB: 15.235%). The increment of rice husk content in hybrid loading lower the elongation at break but accelerate the biodegradability percentage. This is due to the addition of rice husk cause filler agglomerate in the PBAT matrix as well as impart the brittle nature to the composite. The biodegradability of the PBAT/modified starch and PBAT/MTS/ATRH film after 12 weeks showed 91.23% and 91.94 % weight loss, indicating it is biodegradable material. In the compostability test, both samples achieved the same germination rate and normal growth of the onion seeds compared with PBAT (control sample) at the end of 25 days, demonstrating non-toxicity effect towards the composite. The PBAT-based composites with excellent performance and low cost by simple melt-blending method processing will show promising for potential packaging applications.